Association between CAST and MSTN gene polymorphisms with growth traits in Awassi sheep: DOI: 10.48129/kjs.10955 - Bayraktar, Mervan; Shoshin, Omer (Kuwait Journal of Science, 2022)
This study aims to identify the association between CAST/MspI and MSTN/HaeIII polymorphism with growth traits in Awassi sheep. A total of 129 (male and female) Awassi sheep were used in the study. Growth traits (Body weight BW, body length BL, chest depth CD, heart girth HG and withers height WH) were taken from animals at one year old. PCR-RFLP analysis was used to detect CAST polymorphism (Exon 1C/1D) and MSTN (Exon 3) genes. Three genotypes (MM, MN and NN) were observed for CAST/MspI polymorphism with allele and genotype frequency 0.78(M) and 0.22(N); 0.70(MM), 0.16(MN) and 0.14(NN). Two genotypes (MM and mm) were found for MSTN/HaeIII polymorphism with allele and genotype frequency as 0.10(M) and 0.90(N); 0.10(MM) and 0.90(mm). The genes were in agreement with Hardy-Weinberg equilibrium (p>0.05). The association analysis showed an association between CAST/MspI polymorphism and BW, BL, CD, HG and WH (P<0.05; P<0.10). The MM genotypes had the highest BW compared to MN and NN genotypes. Whereas the MN genotypes had the highest BL, CD, HG and WH compared to MM and NN genotypes. No association was found between MSTN/HaeIII polymorphism and growth traits.